Morphological characterization of selected Pulau Perhentian sea cucumbers - Ariffin, Siti Fatihah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
Introduction: Sea cucumber is a marine invertebrate that is closely related to the starfish and sea urchins. There are about 2,000 species of sea cucumbers found everywhere including the deep sea. In Asia, sea cucumber is known as Stichopus spp. which known as 'gamat' in Malaysia. Besides it, common species in North America and Europe are Cucumaria, Ho/othuria, Thyone and Leptosynapta (Barnes, 1991). The interest of this marine animal either their extracts or bodily is to really define the morphological of sea cucumber that found in Pulau Perhentian. Geographical and biodiversity is important factor to properly identified specific species that is really having potential value in local delicious, medical importance and Obstetric & Genocology. Aim and purpose of the study: This study was designed to clarify and characterized the selected Pulau Perhentian sea cucumber by examined their external and internal morphology. The aim to clearly identify each sample taxonomy and anatomy for further future work in pharmacologic effects of their tissue extract. Material and methodology: The sample was harvested at Pulau Perhentian and the morphological study was based on observation using stereomicrograph, light microscope and scanning electron microscope. Result and discussion: There seem to exist in a variable difference in the external and internal morphology at from each specimen observed. The orientation and density of the 'mutable' collagens was in different histological feature especially when comparing at the mouth and its anus. There are highly suggestive present of ossicles and morula cells at the tissue and integument of sample A. Conclusion: Specimen A was highly suggestive as Cucumaria frondosa which reported only found in North America, changes in global climate may not make its finding in Asia impossible.